The effects of response features on failure modes of board level drop impact test - Liu, Y; Sun, F L; Kessels, F J H D; van Driel, W D; Zhang, G Q (2010 11th International Conference on Electronic Packaging Technology and High Density Packaging, 2010)
Portable electronic products are getting popular during last decade. One of the most common failures for a mobile device is related to the accidental drop impact during daily usage. In this paper, responses data of PCB were measured during drop impact; loading features are analyzed with response data; actual drop tests were carried out to obtained actual drop failure data; failure analyses were conducted to determine the failure modes. The failure modes and mechanism were discussed with the response data and actual failure data. Results shows that impact loading response performed as several damping rebound, which results to a combination damage of impact and fatigue. Eigenfrequency dominate the deformation in length direction, while higher modes provide significant contribution to deformation in width direction. Impact damage accumulated in drop test is dependent not only on the strain amplitude but also on the modes contribution. Higher frequency at lower strain level may also produce great damage. Failure modes of drop impact tests showed complexity. Failure sites competing between solder interconnects and RCC layer were observed. The cracks in solder interconnect tend to initiate in the solder bulk. Cracks propagate into imtermetallic layer usually become complete cracks.